2013
DOI: 10.1093/tropej/fmt011
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Perinatal Asphyxia at the University Hospital of Kinshasa (Democratic Republic Of Congo)

Abstract: The incidence of perinatal asphyxia at the University Hospital of Kinshasa remains high and the majority of patients had a severe HIE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
8
18
1
Order By: Relevance
“…In this cohort, the overall hospital mortality rate was 34.3% and occurred more frequently in neonates with acute kidney injury than those without acute kidney injury (50% versus 23%). This finding is similar to previous reports from other developing countries (1,5). Compared to reports from developed countries, the mortality rate in neonates with severe perinatal asphyxia seemed to be higher in our study (14,24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this cohort, the overall hospital mortality rate was 34.3% and occurred more frequently in neonates with acute kidney injury than those without acute kidney injury (50% versus 23%). This finding is similar to previous reports from other developing countries (1,5). Compared to reports from developed countries, the mortality rate in neonates with severe perinatal asphyxia seemed to be higher in our study (14,24).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the proportion of neonates with birth asphyxia diagnosed with acute kidney injury was just under 43%, which is similar to other worldwide studies that have reported 43% to 57% (12)(13)(14)(15), but higher than the 15% to 27% reported in Western countries (16)(17)(18). This difference may be due a lack of training for staff and the delivery of healthcare facilities in DRC (5).…”
Section: Discussionsupporting
confidence: 83%
“…This study aimed to determine the evolution of the Thompson score in neonates with perinatal asphyxia in the first 6 h after birth at the University Hospital of Kinshasa. In a previous study, we described perinatal asphyxia in our hospital with a rate of 88% of HIE . A good correlation was found between the Sarnat and Sarnat grading system and the Thompson score.…”
Section: Discussionmentioning
confidence: 68%
“…There was a consistent predominance of male cases across NE birth cohorts in different regions and mortality levels (pooled proportion adjusted for population sex ratio at birth, 58.7% males (55.6–61.8%)) ( Supplementary Information online). The adjusted proportion of male cases ranged from 48.5% in the Democratic Republic of Congo (57) to 70.6% in Italy (58). The NE sex risk ratios were adjusted for the live birth sex ratio for the year of the study, then pooled by random-effects meta-analysis.…”
Section: Resultsmentioning
confidence: 99%